Exploiting spore-autonomous fluorescent protein expression to quantify meiotic chromosome behaviors in Saccharomyces cerevisiae - Thacker, Drew; Knop, Michael (Genetics, 2011)
The budding yeast Saccharomyces cerevisiae has proven to be a rich source of information about the mechanisms and regulation of homologous recombination during meiosis. A common technique for studying this process involves microdissecting the four products (ascospores) of a single meiosis and analyzing the configuration of genetic markers in the spores that are viable. Although this type of analysis is powerful, it can be laborious and time-consuming to characterize the large numbers of meioses needed to generate statistically robust data sets. Moreover, the reliance on viable (euploid) spores has the potential to introduce selection bias, especially when analyzing mutants with elevated frequencies of meiotic chromosome missegregation. To overcome these limitations, we developed a versatile, portable set of reporter constructs that drive fluorescent protein expression specifically in only those spores that inherit the reporter. These spore-autonomous fluorescence constructs allow direct visualization of inheritance patterns in intact tetrads, eliminating the need for microdissection and permitting meiotic segregation patterns to be ascertained even in aneuploid spores. As proof of principle, we demonstrate how different arrangements of reporters can be used to quantify crossover frequency, crossover interference, gene conversion, crossover/noncrossover ratios, and chromosome missegregation.